Ultrasonic Mediated Synthesis of Dihydropyrano [2, 3-C] Pyrazole Derivatives Catalyzed By Cyanuric Acid/1-Methyl Imidazole (International Journal of Scientific Research in Science and Technology, 2024)
A Novel approach for the synthesis of dihydropyrano[2,3-c] pyrazoles via four-component reaction of ethyl acetoacetate, hydrazine hydrate, aromatic aldehydes and malononitrile at room temperature under ultrasound irradiation is described. The reaction has been catalyzed by cyanuric acid and 1-methyl inidazole in aqueous medium. This protocol afforded several advantages such as easily available catalyst, simple operational procedure, excellent yield and ultrasound irradiation.